Finding creativity in the diversity of environmental ethics - Johan Hattingh (Environmental Association of Southern Africa, 1999)
The contribution is a comprehensive if abbreviated review of different philosophical perspectives on human-environment relationships. Extensively referenced, it outlines historical trends and current debates in the field of environmental ethics. The author argues that the diversity and disagreements amongst environmental philosophers is not a cause for concern, but rather an opening in which new and better positions can be sought, towards a philosophy which can meaningfully enable environmental practice.